(untitled) (Global Journal of Science Frontier Research, 2013)
The purpose of this study was to identify appropriate samples and culture techniques on the isolation of thermophiles from automobile radiators. Water samples from these artificial environments were used for the isolation of thermophilic bacteria at 60Â°C and pH 7.65. Samples from Honda, Jetta and Passat (automobile vehicles) were screened for the growth of thermophilic organisms using nutrient broth medium and their turbidity were measured using spectrophotometer at 600nm. Results of this study suggest that optimal isolation rates of thermophiles from automobile radiator samples were achieved by culturing the sample on nutrient broth and agar at high temperature. Extremophilic microorganisms, especially thermophilic bacteria can facilitate the enzymatic degradation of polymeric substrates such as starch, cellulose, xylan, pectin and chitin.